Übersetzungprobleme und Schwierigkeiten des Transfers von Bedeutungen in einem literarischen Werk - Amel BOUARA (Altralang Journal, 2020)
ABSTRACT: The analysis deals with the theory of translation, as well as with the translation process, which can be regarded as a creative and intercultural process. It represents an art that carries the act of culture and communication The core is the investigation of cultural transfer levels and processes in translations of German literature into Arabic. This work focuses on literary translation. Not only the basic terms of the translation area are clarified, but also the examples of literary translations - from German to Arabic and from Arabic to German - are presented, as well as the difficulties described, which may occur in the process of translation. On the basis of the selected text sections from various literary works (German and Arabic prose texts), the creative activity of a translator is shown and the own translation process is presented. Finally, the present work is intended to help present the literary translation reality in terms of translation skills and difficulties, and to show the solutions.